Feelings and experiences of women with sexually transmitted infections (Revista Contexto & Saúde, 2025)
Objective: to describe the feelings and experiences of women exposed to sexually transmitted infections. Method: qualitative study, conducted with seven women in a reference center for the care of women in a municipality on the western border of Rio Grande do Sul. Data were collected in December 2020, through semi-structured interviews and the Dynamics of Creativity and Sensitivity, submitted to content thematic analysis. Results: participants indicated prejudice and judgment among family members and friends. Regarding transmission, women did not use condoms during sexual intercourse because they had a fixed relationship. Stood out in the lines, the feeling of frustration for not being able to breastfeed their children. Conclusion: the need to disseminate information about sexually transmitted infections is identified, since most of the participants had incipient knowledge on the subject.
Keywords: Sexually Transmitted Infections; Sexual Behavior; Health Vulnerability; Women’s Health; Nursing